A importância dos morcegos na regeneração do meio ambiente: um estudo bibliográfico, um tema para aulas de Ciências - COSTA, Antonielma Sousa da (2024)
This work aims to clarify how bats contribute positively with the development and maintenance of the ecosystem, seeking to explain and demonstrate how this fact occurs and to achieve these objectives the present work will use the bibliographical research and the analysis of sites, theses, articles, etc., as a method to support this research. The results verified on the positive contribution of bats to the environment environment are large and can be organized into three major points: 1) The bats carry out the renewal of the ecosystem through the dissemination of seeds that will grow into trees, 2) Bats perform the pollination that allows the emergence of fruits, 3) Bats do the control of animal and insect species ensuring biological balance. No if you can, therefore, destroy bats, you must therefore leave them alive, for the ecological niches that they play are fundamental for nature to be in ecological balance. Hence the importance of bats during classes of Science, teachers should give emphasis to these mammals, since they can be a generating theme for content such as: Environment, food chain, ecological niche, germination, sexual and asexual reproduction, etc.